A comprehensive assessment of endocrine-disrupting chemicals in an Indian food basket: Levels, dietary intakes, and comparison with European data - Sharma, Brij Mohan; Bharat, Girija K; Chakraborty, Paromita; Martiník, Jakub; Audy, Ondřej; Kukučka, Petr; Přibylová, Petra; Kukreti, Praveen Kumar; Sharma, Anežka; Kalina, Jiří; Steindal, Eirik Hovland; Nizzetto, Luca (Environmental pollution (Barking, Essex, 2021)
Endocrine-disrupting chemicals (EDCs) in diet are a health concern and their monitoring in food has been introduced in the European Union. In developing countries, EDC dietary exposure data are scarce, especially from areas perceived as pollution hotspots, including industrialized countries like India. Several persistent organic pollutants (POPs) act as EDCs and pose a pressure to human health mainly through dietary exposure. In the present study, a range of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), dioxins and furans were measured in several food items collected from Indian urban (Delhi) and peri-urban (Dehradun) areas. Food basket contamination data were used to estimate EDC dietary exposure and compare it with that of the average European population estimated from available monitoring data. All the target contaminants were found in most food items, especially in dairies and meat products. OCPs were the main contributers to the measured EDC contamination. Food supplied to Delhi's markets had higher EDC contamination than that supplied to the peri-urban market in Dehradun. Despite lax compliance and control measures, Indian dietary exposure of OCPs and PBDEs were comparable with that of Europe and were lower for PCBs and dioxins. Higher meat consumption in Europe only partly explained this pattern which was driven also by the higher EDC residues in some European food items. A substantial part of endocrine disrupting potential in the diet derives from food and animal feeds internationally traded between developed and developing countries. With increasingly globalized food systems, internationally harmonized policies on EDC content in food can lead to better protection of health in both these contexts.
Keywords: Indian food basket; polychlorované bifenyly; halogenované difenylethery; Humans; přijímání potravy; chlorované uhlovodíky; Eating; Endocrine Disruptors; Environmental Monitoring; Hydrocarbons, Chlorinated; Halogenated Diphenyl Ethers; lidé; zvířata; látky znečišťující životní prostředí; Human exposure; monitorování životního prostředí; endokrinní disruptory; Environmental Pollutants; Endocrine-disrupting chemicals (EDCs); kontaminace potravin; Food Contamination; Stockholm Convention; Animals; Food contamination; Persistent organic pollutants (POPs); Polychlorinated Biphenyls